Mobility and the transiency of social spaces: african merchant entrepreneurs in China - Bork-Hüffer, Tabea; Rafflenbeul, Birte; Zhigang, Li; Kraas, Frauke; Xue, Desheng (Population, space and place, 2016)
This paper investigates how China's heterogeneous African population contributes to shaping new types of social spaces in Chinese cities. We analyse how their different types of collective (primary and corporate) agency work in the creation of transient spaces, that is, translocal and transforming spaces in Guangzhou and Foshan, China. A mixed-methods research approach was applied to cover the breadth and depth of African merchants' social spaces in both cities. The results indicate that many African merchants are mobile individuals linked across China and across national borders to their home countries and other countries in which they have lived and worked. Whereas other authors have looked into traders' migration pathways via Southeast Asia, Hong Kong, and Macao to China, our results also stress the importance of previous intermediate stations, particularly in West African states, South Africa, and Dubai. The transiency of the social spaces of Africans is underlined by the high mobility of many of them, including the great inflow of new migrants with trajectories that are often informed by living in or experiencing a variety of other societies, business environments, and living and working conditions. Through their translocal and transnational activities, experiences, and trajectories, African merchants contribute to the emergence of new transient spaces in both cities, as well as to successful business performance, which also benefits the Chinese economy and society. Copyright © 2015 John Wiley & Sons, Ltd.